Potensi Senyawa Antimikrobia Simplisia Teripang Pasir (Holothuria scabra) Terhadap Penghambatan Pertumbuhan Bakteri - Nikman Azmin; Muh. Nasir (Jompa Research and Development, 2024)
Helicobacter pylori bacteria is a pleomorphic bacteria that can cause wounds and bruising in the stomach, and even lead to cancer. The use of antibiotics in the eradication of Helicobacter pylori has the effect of causing the body to become resistant to antibiotics and the global crisis has caused treatment costs to become increasingly expensive at this time. Therefore, it is necessary to think about ways to find new alternative treatments to control the growth and infection caused by Helicobacter pylori bacteria, such as traditional medicines which have the potential to have damaging effects on genes. The Ministry of Health has launched a traditional medicine development program towards phytotherapy group medicines. One natural ingredient that is thought to contain active antibacterial ingredients is sea cucumber. Sea cucumbers have long been used as a source of traditional medicine. The research results show that there are several zones of resistance from sand sea cucumber simplicia (Holothuria scabra) to inhibit the growth of Helicobacter pylori. Then there was also a change in the DNA integrity profile of the Helicobacter pylori gene due to the effect of the sand sea cucumber simplicia (Holothuria scabra), namely by not forming DNA bands.